Solid-state batteries and electrical equipment

By setting a negative electrode interface modification layer between the negative electrode and the solid electrolyte layer of the solid state battery, the interface modification layer formed by metal nitride and carbon material is solved, and the cycle stability and life of the battery are significantly improved.

CN115207483BActive Publication Date: 2025-03-18SUNWODA ELECTRONICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210890724.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2025-03-18
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

The interface chemical stability between the solid electrolyte layer and the metal lithium negative electrode has poor interface chemical stability, large interface impedance, and easy growth of lithium dendrites, which affects the performance and cycle life of the battery.

Method used

A negative electrode interface modification layer is provided between the negative electrode and the solid electrolyte layer. By adding metal nitride and carbon material to the buffer layer, after the battery is melted, the metal nitride forms a metal lithium alloy and Li3N, and together with the carbon material, a negative electrode interface modification layer is formed to prevent direct contact between the solid electrolyte and the metal lithium negative electrode.

Benefits of technology

Significantly improve the interface stability on the negative electrode side, inhibit the growth of lithium dendrites, and improve the utilization rate and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115207483B_ABST
    Figure CN115207483B_ABST
Patent Text Reader

Abstract

The present application discloses a solid-state battery and an electrical device. The solid-state battery includes a positive electrode, a negative electrode, a solid electrolyte layer and a negative electrode interface modification layer. The negative electrode interface modification layer is arranged between the negative electrode and the solid electrolyte layer. The negative electrode interface modification layer includes: a self-supporting structure layer, which is mainly composed of carbon materials; metal lithium alloy and lithium nitride, which are distributed inside and on the surface of the self-supporting structure layer. The presence of the negative electrode interface modification layer can prevent the direct contact between the solid electrolyte and the metal lithium; in addition, the carbon material in the negative electrode interface modification layer can conduct both lithium ions and electrons; the metal lithium alloy promotes the transmission of lithium ions in the interface layer; lithium nitride has good ion conductivity; therefore, by arranging the negative electrode interface modification layer between the negative electrode and the solid electrolyte layer, the growth of lithium dendrites can be suppressed, the metal lithium negative electrode can be protected, and the cycle stability of the negative electrode and the cycle life of the solid-state battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of secondary batteries, and specifically to solid-state batteries and electrical equipment. Background Art

[0002] The metallic lithium anode has a low chemical potential (-3.04 V vs. SHE) and a high theoretical capacity (3860 mAh g -1 ) and other advantages, and has always been considered the most ideal negative electrode material for lithium batteries. However, the high activity of metallic lithium and the lithium dendrites formed during battery cycling have seriously affected the commercialization process of metallic lithium negative electrodes.

[0003] Solid-state batteries are considered to be an effective way to overcome lithium dendrites. They use solid electrolytes with high mechanical strength to inhibit the penetration of lithium dendrites. However, most solid electrolytes are unstable to metallic lithium. During standing and cycling, an interface layer will be formed, which consumes metallic lithium. Moreover, the interface layer has high impedance, which reduces the performance of the battery and causes battery failure. Based on this, it is urgent to propose a solid-state battery that can reduce the interface impedance between the solid electrolyte layer and the metallic lithium negative electrode. Summary of the invention

[0004] The present application aims to solve the problems of poor interface chemical stability between the solid electrolyte layer and the metal lithium negative electrode, large interface impedance, and easy growth of lithium dendrites, and provides a solid-state battery with a negative electrode interface modification layer. By adding metal nitride and carbon material to the buffer layer, after battery formation, the metal nitride generates a metal lithium alloy and Li3N, and forms a negative electrode interface modification layer together with the carbon material, so as to prevent the direct contact between the solid electrolyte and the metal lithium negative electrode, significantly improve the interface stability on the negative electrode side, facilitate the deposition of lithium ions in the solid-state battery during the cyclic charge and discharge process, inhibit the growth of lithium dendrites, and thus improve the battery utilization and cycle life.

[0005] The solid-state battery provided in the present application comprises a positive electrode, a negative electrode, a solid electrolyte layer and a negative electrode interface modification layer, wherein the negative electrode interface modification layer is arranged between the negative electrode and the solid electrolyte layer, and the negative electrode interface modification layer comprises a self-supporting structure layer, and the self-supporting structure layer is mainly composed of a carbon material;

[0006] Metal lithium alloy and lithium nitride, wherein the metal lithium alloy and the lithium nitride are distributed inside and on the surface of the self-supporting structure layer.

[0007] Furthermore, based on the mass of the negative electrode interface modification layer, the carbon material accounts for 70-90%, the metal lithium alloy accounts for 1-20%, and the lithium nitride accounts for 0.01-10%.

[0008] Furthermore, the metal lithium alloy includes one or more of silver-lithium alloy, tin-lithium alloy, titanium-lithium alloy, zinc-lithium alloy and zirconium-lithium alloy.

[0009] Furthermore, the carbon material is selected from one or more of conductive carbon black, graphene, and vapor-grown carbon fiber.

[0010] Furthermore, the thickness of the negative electrode interface modification layer may be 1 to 20 μm, preferably 5 to 10 μm.

[0011] Furthermore, the porosity of the interface modification layer is between 1% and 5%.

[0012] The carbon material in the negative electrode interface modification layer serves as a skeleton structure and can conduct both lithium ions and electrons; the metal lithium alloy promotes the transmission of lithium ions in the interface layer, and lithium nitride has good ion conductivity, inhibits the growth of lithium dendrites, protects the metal lithium negative electrode, and improves the cycle stability of the metal lithium negative electrode.

[0013] The negative electrode interface modification layer is located between the solid electrolyte and the lithium metal negative electrode, which can prevent the solid electrolyte from directly contacting the lithium metal, significantly improve the interface stability of the lithium metal negative electrode side, inhibit the growth of lithium dendrites, and increase the cycle life of the battery.

[0014] Furthermore, the method for obtaining the negative electrode interface modification layer in the application includes:

[0015] The application is to mix metal nitride, carbon material, adhesive and solvent to prepare a composite buffer layer;

[0016] The metal nitride in the composite buffer layer is converted into a metal lithium alloy and lithium nitride through an in-situ electrochemical reaction to obtain the negative electrode interface modification layer.

[0017] Furthermore, the metal nitride includes one or more of Ag3N, Sn3N2, AlN, Ti3N4, Zn3N2, and Zr3N4.

[0018] Furthermore, in the composite buffer layer, the metal nitride accounts for 1 to 10 parts by weight; the carbon material accounts for 70 to 90 parts by weight; and the adhesive accounts for 3 to 10 parts by weight.

[0019] The present application also provides an electrical device.

[0020] The electrical equipment includes the above-mentioned solid-state battery.

[0021] Compared with the prior art, the beneficial effects of this application are:

[0022] The solid-state battery of the present application has a negative electrode interface modification layer between the negative electrode and the solid electrolyte layer, and the presence of the negative electrode interface modification layer can prevent the direct contact between the solid electrolyte and the metallic lithium. In addition, the carbon material in the negative electrode interface modification layer can conduct both lithium ions and electrons, and the metallic lithium alloy also promotes the transmission of lithium ions in the interface layer, while lithium nitride has good ion conductivity. Therefore, by providing a negative electrode interface modification layer between the negative electrode and the solid electrolyte layer, the growth of lithium dendrites can be effectively inhibited, the metallic lithium negative electrode can be protected, and the cycle stability and cycle life of the solid-state battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0024] Figure 1 A schematic structural diagram of a solid-state battery according to an embodiment of the present application is shown.

[0025] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with specific embodiments. The examples given are only for illustrating the present application, not for limiting the scope of the present application. The examples provided below can be used as a guide for further improvements by ordinary technicians in the technical field, and do not constitute a limitation of the present application in any way.

[0027] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0028] See attached Figure 1 The present embodiment provides a solid-state battery, comprising a positive electrode 2, a negative electrode 1, a solid electrolyte layer 4 and a negative electrode interface modification layer 3, wherein the negative electrode interface modification layer 3 is disposed between the negative electrode 1 and the solid electrolyte layer 4, and the negative electrode interface modification layer 3 comprises:

[0029] A self-supporting structural layer, wherein the self-supporting structural layer is mainly composed of a carbon material;

[0030] Metal lithium alloy and lithium nitride, wherein the metal lithium alloy and the lithium nitride are distributed inside and on the surface of the self-supporting structure layer.

[0031] In this embodiment, the carbon material can isolate the contact between the metal lithium and the sulfide electrolyte, inhibiting the interface side reaction; the metal lithium alloy can promote the conduction of lithium ions and improve the ion conductivity of the interface layer; lithium nitride can protect the metal lithium negative electrode, inhibit the occurrence of side reactions, and at the same time has a high ion conductivity to ensure the lithium ion conductivity.

[0032] In another embodiment, in order to further improve the cycle stability of the solid-state battery and further inhibit the growth of negative electrode lithium dendrites, based on the mass of the negative electrode interface modification layer, the carbon material accounts for 70-90%, the metal lithium alloy accounts for 1-20%, and the lithium nitride accounts for 0.01-10%.

[0033] In another embodiment, the metal lithium alloy includes one or more of a silver-lithium alloy, a tin-lithium alloy, a titanium-lithium alloy, a zinc-lithium alloy, and a zirconium-lithium alloy. The metal lithium alloys involved above have excellent electrical conductivity, can improve the conductivity of the negative electrode interface modification layer, and can improve the charge and discharge rate of the solid-state battery. In addition, the metal lithium alloy can also give the interface modification layer strong mechanical properties, thereby improving the physical stability of the negative electrode interface modification layer and preventing the negative electrode interface modification layer from being easily pierced.

[0034] In another embodiment, the thickness of the negative electrode interface modification layer is 1-20 μm, for example, 1-5 μm, 5-10 μm, 8-12 μm, 10-20 μm, 8 μm, 12 μm, 17 μm, preferably 5-10 μm.

[0035] When the negative electrode interface layer is too thin, the interface resistance is low, but the stability of the interface layer is poor, and the metal lithium dendrites will pierce the interface modification layer quickly, causing the battery to short circuit and fail; when the interface layer is too thick, the interface resistance increases, but the interface layer has good stability and the battery cycle life is long; when the thickness of the negative electrode interface modification layer is preferably 5 to 10 μm, the battery internal resistance and cycle life reach the optimal value of balance.

[0036] The porosity of the interface modification layer is between 1% and 5%.

[0037] The larger the porosity of the interface layer, the worse the ion conductivity of the interface layer, the higher the interface resistance, the lower the cycle life, and the easier it is for lithium dendrites to pierce the interface modification layer and the electrolyte layer, causing battery short circuit failure.

[0038] In another embodiment, the method for obtaining the negative electrode interface modification layer includes:

[0039] S1, mixing metal nitride, carbon material, adhesive and solvent to prepare a composite buffer layer;

[0040] S2. Converting the metal nitride in the composite buffer layer into a metal lithium alloy and lithium nitride through an in-situ electrochemical reaction to obtain the negative electrode interface modification layer.

[0041] In this embodiment, the metal nitride is selected from one or more of Ag3N, Sn3N2, AlN, Ti3N4, Zn3N2, and Zr3N4. The above metal nitrides can be transformed into lithium metal alloy materials with excellent electrical conductivity and mechanical properties after battery formation.

[0042] The carbon material is selected from one or more of SP, graphene, and VGCF;

[0043] The binder is selected from one or more of CMC, PVA, PAA, SBR, PEO, and PVDF;

[0044] In one embodiment, step S1 includes the following steps:

[0045] S11, mixing the metal nitride, the carbon material, the binder and the solvent in proportion, and stirring and dispersing them to obtain a composite buffer layer slurry;

[0046] S12, coating the composite buffer layer slurry on one side of a sacrificial substrate, and drying the composite buffer layer to obtain the composite buffer layer, wherein the composite buffer layer is supported on the sacrificial substrate.

[0047] Step S2 includes the following steps:

[0048] S21, covering one side of the composite buffer layer with a solid electrolyte, and pressing the composite buffer layer and the solid electrolyte together through a pressing process;

[0049] S22, removing the sacrificial substrate;

[0050] S23, assembling the negative electrode, the positive electrode and the composite buffer layer covered with the solid electrolyte into an initial solid-state battery; the negative electrode comprises a lithium metal negative electrode;

[0051] S24, performing activation treatment on the initial solid-state battery, and after activation, the metal nitride in the composite buffer layer is converted into a metal lithium alloy and lithium nitride, so as to obtain a solid-state battery having the negative electrode interface modification layer.

[0052] In one embodiment, the metal lithium alloy includes one or more of silver-lithium alloy, tin-lithium alloy, titanium-lithium alloy, zinc-lithium alloy and zirconium-lithium alloy.

[0053] The activation treatment includes high temperature activation, the temperature of the high temperature activation is 60-150° C., and the activation time is 2-12 hours.

[0054] The above acquisition method does not need to consider the influence of the solvent on the electrolyte layer and the metallic lithium negative electrode during the preparation of the interface modification layer. For example, polar solvents such as acetonitrile cannot be used to directly prepare the modification layer on the surface of the sulfide electrolyte. Solvents such as water and ethanol will react with metallic lithium and cannot prepare the modification layer on the surface of metallic lithium. Therefore, this method broadens the range of solvent selection.

[0055] The present application also provides an electrical device, which comprises the above-mentioned solid-state battery.

[0056] In one embodiment, the solid electrolyte layer includes lithium germanium phosphorus sulfide, 70Li2S·30P2S5, Li 11 Si2P1S 12 , Li 10 SnP2S 12 The solid electrolyte has excellent ion conductivity, which can increase the migration speed of lithium ions, thereby improving the electrochemical performance of the battery.

[0057] In one embodiment, the porosity of the solid electrolyte layer is 2% to 10%, which can reduce the internal resistance of the battery and extend the life of the metal lithium negative electrode.

[0058] In one embodiment, the ratio of the thickness of the solid electrolyte layer to the thickness of the interface modification layer is in the range of 1000:(1-20). Within this range, the transmission path of lithium ions can be reduced, the transmission efficiency can be improved, and thus the charge and discharge performance and cycle performance of the battery can be improved.

[0059] In the present application, the presence of the negative electrode interface modification layer can prevent direct contact between the solid electrolyte and metallic lithium; in addition, the carbon material in the negative electrode interface modification layer can conduct both lithium ions and electrons; metallic lithium alloys promote the transmission of lithium ions in the interface layer; lithium nitride has good ion conductivity; therefore, by providing a negative electrode interface modification layer between the negative electrode and the solid electrolyte layer, the growth of lithium dendrites can be inhibited, the metallic lithium negative electrode can be protected, and the cycle stability of the negative electrode and the cycle life of the solid-state battery can be improved.

[0060] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0061] Embodiment 1,

[0062] Preparation of solid-state batteries with negative electrode interface modification layers:

[0063] (1) Ag3N (10 wt%), carbon material (SP, 87 wt%), PVDF (3 wt%) and NMP were mixed and stirred to obtain a composite buffer layer slurry;

[0064] (2) applying the composite buffer layer slurry onto a sacrificial substrate (Al foil) through a doctor blade coating process, with a coating thickness of 60 μm, and drying to obtain a sacrificial substrate loaded with the composite buffer layer;

[0065] (3) 100 mg of lithium germanium phosphide Li 10 GeP2S5 (LGPS) powder (particle size 5 μm) is pressed at a pressure of 360 MPa for 1 min to obtain a solid electrolyte sheet, at which the porosity of the solid electrolyte sheet is 5% and the thickness of the solid electrolyte sheet is 1000 μm; the solid electrolyte sheet is covered on the sacrificial substrate loaded with the composite buffer layer; cold pressing is performed at a pressure of 200 MPa for 1 min to press the composite buffer layer and the solid electrolyte sheet tightly together;

[0066] (4) mechanically peeling the sacrificial substrate from the composite buffer layer so that the composite buffer layer is applied to the solid electrolyte side;

[0067] (5) Assembling a solid-state symmetrical battery: applying lithium metal to both sides of a solid electrolyte modified with a buffer layer;

[0068] (6) The obtained symmetrical battery is placed at 100°C for 6 hours for high temperature activation. After activation, the Ag3N in the composite buffer layer reacts with the metal lithium to generate Li3N and silver-lithium alloy, forming a solid-state battery with a negative electrode interface modification layer. The porosity of the negative electrode interface modification layer is 1%; the thickness of the negative electrode interface modification layer is 10 μm. In the negative electrode interface modification layer, the carbon material accounts for 86.825%, the silver-lithium alloy accounts for 9.585%, and the lithium nitride accounts for 0.615%.

[0069] Example 2

[0070] The difference between this embodiment and embodiment 1 is that Sn3N2 is used instead of Ag3N.

[0071] Example 3

[0072] The difference between this embodiment and embodiment 1 is that Ti3N4 is used instead of Ag3N.

[0073] Example 4

[0074] The difference between this embodiment and embodiment 1 is that Zn3N2 is used instead of Ag3N.

[0075] Example 5

[0076] The difference between this embodiment and embodiment 1 is that Zr3N4 is used instead of Ag3N.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 1 is that the content of Ag3N is adjusted to 1.1wt%, and the content of carbon material is adjusted to 89.9wt%.

[0079] Example 7

[0080] The difference between this embodiment and embodiment 1 is that the content of Ag3N is adjusted to 5wt%, and the content of carbon material is adjusted to 90wt%.

[0081] Example 8

[0082] The difference between this embodiment and embodiment 1 is that the content of Ag3N is adjusted to 13wt%, and the content of carbon material is adjusted to 84wt%.

[0083] Example 9

[0084] The difference between this embodiment and embodiment 1 is that the content of Ag3N is adjusted to 15wt%, and the content of carbon material is adjusted to 82wt%.

[0085] Example 10

[0086] The difference between this embodiment and embodiment 1 is that the content of Ag3N is adjusted to 20wt%, and the content of carbon material is adjusted to 77wt%.

[0087] Embodiment 11

[0088] The difference between this embodiment and embodiment 1 is that the content of Ag3N is adjusted to 50wt%, and the content of carbon material is adjusted to 47wt%.

[0089] Example 12

[0090] The difference between this embodiment and embodiment 1 is that the coating thickness of the interface layer slurry is 5 micrometers, and the thickness of the interface modification layer is adjusted to 1 micrometer.

[0091] Embodiment 13

[0092] The difference between this embodiment and embodiment 1 is that the coating thickness of the interface layer slurry is 50 microns, and the thickness of the interface modification layer is adjusted to 5 microns.

[0093] Embodiment 14

[0094] The difference between this embodiment and embodiment 1 is that the coating thickness of the interface layer slurry is 200 microns, and the thickness of the interface modification layer is adjusted to 20 microns.

[0095] Embodiment 15

[0096] The difference between this embodiment and embodiment 1 is that the coating thickness of the interface layer slurry is 600 microns, and the thickness of the interface modification layer is adjusted to 100 microns.

[0097] Example 16

[0098] The difference between this embodiment and embodiment 1 is that the cold pressing pressure is changed to 150 MPa, so that the porosity of the negative electrode interface modification layer is 2%.

[0099] Embodiment 17

[0100] The difference between this embodiment and embodiment 1 is that the cold pressing pressure is changed to 100 MPa, so that the porosity of the negative electrode interface modification layer is 5%.

[0101] Embodiment 18

[0102] The difference between this embodiment and embodiment 1 is that the carbon material is graphene.

[0103] Embodiment 19

[0104] The difference between this embodiment and embodiment 1 is that the carbon material is VGCF (vapor grown carbon fiber).

[0105] Embodiment 20

[0106] The difference between this embodiment and embodiment 1 is that the binder is CMC (carboxymethyl cellulose).

[0107] Embodiment 21

[0108] The difference between this embodiment and embodiment 1 is that the binder is PVA (polyvinyl alcohol).

[0109] Comparative Example 1

[0110] This comparative example does not contain an interface modification layer, and the rest is the same as Example 1.

[0111] Comparative Example 2

[0112] This comparative example does not contain carbon material, and the rest is the same as Example 1.

[0113] Comparative Example 3

[0114] This comparative example does not contain metal nitride, and the other parts are the same as those in Example 1.

[0115] By adjusting relevant parameters, solid-state batteries with negative electrode interface modification layers having different characteristics are obtained. The different parameters of the solid-state batteries prepared in the above embodiments 1 to 23 and comparative examples 1 to 3 are recorded, and performance tests are performed respectively.

[0116] The symmetrical battery performance test method is as follows: At room temperature, a 10mA blue electric charge and discharge test device is used to test the symmetrical battery performance, and the charge and discharge current density is 0.1mA / cm 2 , the charge and discharge capacity is 0.1mAh / cm 2The test data and test results (polarization voltage and lithium stability cycle time test results) are shown in Table 1. In this application, the test results of lithium stability cycle indicate the cycle time of the symmetrical battery when the positive and negative electrodes are short-circuited during the symmetrical battery charge and discharge cycle, which can characterize the service life of the symmetrical battery.

[0117] Table 1:

[0118]

[0119] It can be seen from the embodiments and comparative examples in Table 1 that the negative electrode interface modification layer described in the present application is arranged between the metal lithium negative electrode and the solid electrolyte, which can reduce the interface impedance, which is manifested as a lower polarization voltage (≤0.05V) and can prolong the lithium stability cycle time (≥1000h), thereby improving the interface chemical stability between the solid electrolyte and the metal lithium negative electrode, reducing lithium dendrites and reducing the interface impedance.

[0120] Comparing Examples 1 to 5, it can be seen that the present application has no special requirements on the type of metal in the metal nitride, and any metal that can form an alloy with metallic lithium can be used in the present application.

[0121] By comparing Example 1 with Examples 6 to 11, it can be seen that the content of metal nitride varies within the range of 1% to 20%. Correspondingly, the content of metal lithium alloy varies within the range of 1-20%. If the content of metal nitride is too high, the ionic conductivity of the interface layer before formation will be greatly reduced, resulting in too much polarization voltage in the early stage of formation. As the content of metal lithium alloy increases, the polarization voltage shows an upward trend, and the cycle life first increases and then decreases with the increase of metal nitride.

[0122] By comparing Example 1 with Examples 12 to 15, it can be seen that an increase in the thickness of the interface layer will lead to an increase in the polarization voltage of the symmetrical battery and increase the cycle life of the symmetrical battery; when the negative electrode interface layer is too thin, the interface resistance is low, but the stability of the interface layer is poor, and the metal lithium dendrites will pierce the interface modification layer quickly, causing the battery to short-circuit and fail; when the interface layer is too thick, the interface resistance increases, but the interface layer has good stability and the battery cycle life is long; when the thickness of the negative electrode interface modification layer is preferably 5-10μm, the battery internal resistance and cycle life reach an optimal value of balance.

[0123] By comparing Example 1 with Examples 16 to 17, it can be seen that increasing the porosity of the interface layer will increase the polarization voltage of the symmetrical battery and reduce the cycle life of the symmetrical battery.

[0124] By comparing Example 1 with Examples 18 to 19, it can be seen that the better the conductivity of the carbon material, the smaller the polarization voltage of the symmetrical battery, and the longer the life of the symmetrical battery. The specific carbon materials listed in this application can meet the requirements.

[0125] By comparing Example 1 with Examples 20 to 21, it can be seen that the stronger the bonding ability of the binder is, the better the mechanical strength of the modified layer is, and the better the life of the symmetrical battery is.

[0126] By comparing Example 1 and Comparative Example 1, it can be seen that the interface modification layer can reduce the polarization voltage of the symmetrical battery and increase the cycle life of the symmetrical battery.

[0127] By comparing Example 1 and Comparative Example 2, it can be seen that the absence of carbon material will increase the internal resistance of the symmetrical battery, resulting in an increase in the polarization voltage and a decrease in the cycle life of the symmetrical battery.

[0128] By comparing Example 1 and Comparative Example 3, it can be seen that the absence of metallic lithium alloy and lithium nitride will reduce the cycle life of the symmetrical battery.

[0129] The present application has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present application, and without the need to carry out unnecessary experimental conditions, the present application can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present application provides specific embodiments, it should be understood that further improvements can be made to the present application. In a word, according to the principles of the present application, the present application is intended to include any changes, uses or improvements to the present application, including departure from the disclosed scope in the present application and changes made with conventional techniques known in the art.

Claims

1. A solid-state battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a solid electrolyte layer and a negative electrode interface modification layer, wherein the negative electrode interface modification layer is arranged between the negative electrode and the solid electrolyte layer, and the negative electrode interface modification layer comprises: A self-supporting structural layer, wherein the self-supporting structural layer is mainly composed of a carbon material; Metal lithium alloy and lithium nitride, wherein the metal lithium alloy and the lithium nitride are distributed inside and on the surface of the self-supporting structure layer; Based on the mass of the negative electrode interface modification layer, the carbon material accounts for 70-90%, the metal lithium alloy accounts for 1-20%, and the lithium nitride accounts for 0.01-10%; The thickness of the negative electrode interface modification layer is 5-10 μm; The porosity of the interface modification layer is between 1% and 5%; The porosity of the solid electrolyte layer is 2% to 10%; The ratio of the thickness of the solid electrolyte layer to the thickness of the negative electrode interface modification layer is in the range of 1000:(1-20).

2. The solid-state battery according to claim 1, characterized in that: The metal lithium alloy includes one or more of a silver-lithium alloy, a tin-lithium alloy, a titanium-lithium alloy, a zinc-lithium alloy and a zirconium-lithium alloy.

3. The solid-state battery according to claim 1, characterized in that: The carbon material is selected from one or more of conductive carbon black, graphene, and vapor-grown carbon fiber.

4. The solid-state battery according to claim 1, characterized in that: The method for obtaining the negative electrode interface modification layer includes: The metal nitride, the carbon material, the adhesive and the solvent are mixed to prepare a composite buffer layer; The metal nitride in the composite buffer layer is converted into a metal lithium alloy and lithium nitride through an in-situ electrochemical reaction to obtain the negative electrode interface modification layer.

5. The solid-state battery according to claim 4, characterized in that: The metal nitride includes one or more of Ag3N, Sn3N2, AlN, Ti3N4, Zn3N2, and Zr3N4.

6. The solid-state battery according to claim 4, characterized in that: In the composite buffer layer, the metal nitride accounts for 1 to 10 parts by weight; the carbon material accounts for 70 to 90 parts by weight; and the adhesive accounts for 3 to 10 parts by weight.

7. An electrical equipment, characterized in that: The electrical equipment comprises the solid-state battery according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Lithium metal protective layer and preparation method thereof and battery with protective layer

    CN111490252A

  • Modified diaphragm for metal lithium negative electrode and preparation method and application thereof

    CN112635915A

  • Solid-state metal lithium battery with negative electrode interface modification layer

    CN113809386A